Chemical Mutagenesis and Cytogenetic Chromosomal Abnormalities in a Population Living in the Aral Sea region - Sabirov, Zh.; Namazbaeva, Z.; Battakova, Sh.; Otarbayeva, M.; Mukasheva, M.; Yeshmagambetova, A. (Open Access Macedonian Journal of Medical Sciences., 2020)
AIM: The article presents the results of a study of chromosomal mutations in residents living in the Aral Sea disaster zone, using the example of the city of Aralsk. METHODS: The article identifies the level of chromosomal aberrations (CA) in the surveyed population and identifies the leading type of aberrations in this region. RESULTS: Researches have shown that the main types of structural changes were chromatid breaks and single fragments of chromosomes. The results showed that in the study population, the microelement status indicates an imbalance of microelements. A correlation analysis showed a relationship between the nickel content in the blood and the increase in CAs. Furthermore, researches show a hypothesis about the pathogenesis mechanism of the formation of CAs. CONCLUSION: Thus, the article provides information on chromosomal mutations during chemical mutagenesis.
Keywords: DNA; Chromosomal aberrations; Heavy metals; Genotoxicity; Mutagenesis; Aral sea region